PERBANDINGAN MODEL PREDIKSI KEBANGKRUTAN :“Model Altman Z-Score, Foster F-Score, Springate S-Score, Ohlson Y-Score, Zmijewski X-Score, Fullmer H-Score, Zavgreen Pi Score, dan Grover G-Score” - Muhamad Nasir; kamaludin; Pratana Puspa Midiastuty (Jurnal Ilmu Akuntansi, 2024)
ABSTRACT This study aims to test the accuracy of predicting corporate bankruptcy models: (1) Altman Z Score which includes Altman, modified Altman, and modified Altman (2) Foster F-Score, (3) Springate S-Score, (4) Ohlson Y-Score, (5) Zmijewski X-Score, (6) Fullmer H-Score, (7) Zavgreen Pi Score, and (8) Grover G-Score. The research sample covers the period 2010-2016 and uses a sample of non-financial companies listed on the Indonesia Stock Exchange (IDX). The number of observations used in this study was 1421 observations. From the overall test results, the accuracy results for companies that are predicted to be healthy and the order of accuracy are bankruptcy prediction Model 1) Zmijewski X-Score (99.50%), 2) Ohlson Y-Score (98.40%) 3) Fullmer H-Score (93.10%) 4) Grover G-Score (93%) 5) Altman Modified Z'-Score (82.77%) 6) Zavgreen Pi-Score (82.60%) 7) Altman Revised Z'-Score (67.75%) 8) Altman First Z-Score (64.11%) 9) Springate S-Score (58.60%) and 10) Foster F-Score (40.70%).  Testing for companies that are delisted later and from the bankruptcy prediction model declared bankrupt companies obtained the order of prediction accuracy is model prediction 1) Foster F-Score (68.25%) 2) Springate S-Score (61.90%) 3) Altman First Z-Score (26.42%) 4) Altman Revised Z'-Score (25.53%) 5) Fullmer H-Score (22.22%) 6) Zavgreen Pi-Score (20.63%) 7) Altman Modified Z"-Score (16.07%) 8) Grover G-Score (12.70%) 9) Ohlson Y-Score (3.17%) and 10) Zmijewski X-Score (0%).